Low levels of vitamin D in population exposed to significant environmental pollution - Richter, Josef; Větvička, Václav; Král, Vlastimil; Šíma, Petr; Stiborová, Iva; Richterová, Stanislava; Dobiášová, Lucie Rajnohová (Casopis lekaru ceskych, 2023)
In recent years, monitoring of vitamin D levels and possible use of supplementation is gaining attention. Numerous studies showed low levels of vitamin D in winter months followed by improvement during summer. These changes are mostly dependent on the level of sun exposure, but also on geographical location, genetic factors, social-economic status, quality of nutrition and environmental pollution. In this observation we found significant decrease in vitamin D levels in populations exposed to extreme environmental pollution in area of central Europe. This region is known for extreme burden from microparticles originating in chemical industry, surface coal mining and cold-based power stations. Vitamin D levels in all patients was determined by ELISA. Using 540 patients in our department of clinical immunology and allergology we measured the levels of vitamin D in 2016 to 2021 period. In only 4 patients (0.74 %) we found vitamin D levels higher than 30 ng/ml. The curve of observed values does not reflect dependency on sun exposure and does not change during the year. We discuss the effect of environmental contaminants, lifestyle and economic and social factors. From our observations, we propose to directly supplement population with vitamin D, particularly children and seniors. From our observations, we propose to directly supplement population with vitamin D, particularly children and seniors.
Keywords: Vitamin D; Child; Environmental Pollution; health risk; Pollution; ELISA; Humans; vitamin; lidé; vitamin D; znečištění životního prostředí; Vitamins; vitaminy; environment; dítě; Europe; Evropa; Enzyme-Linked Immunosorbent Assay